Pengaruh Harga dan Promosi terhadap Keputusan Pembelian Sepeda Motor Bekas di Showroom Kurnia Indah Maumere - Maria Erliana; Antonius Philipus Kurniawan; Yosef Tonce (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This study aimed to (1) determine how much the Price and Promotion influence on Purchasing Desiciond for used motorbikes at Showroom Krnia Indah Motor Mamere (2) analyze the effect of price and promotion on purchasing decisions for used motorbikes and promotion and purchasing decision for used motorbikes at the Showroom Kurnia Indah Motor Maumere both partially and simltaneosly. The research population was Showroom Kurnia Indah Motor Maumere consumers, as many as 32 people. Due to limited poplation, then this research was conducted by cencus or saturated sampling. Data was collected throght questionnaires and analyzed using descriptive and statistic inferential methods, namely multiple linear regression Hypothesis testing was done throght the F and t-test. Based on descriptive analysis, it reveals that the Purchasing, Price and Promotion variables were categorized as good. The statistical results of thet-tests shows that partially the Price variable had a positive and significant effect on the Purchasing Decision variable. While promotion had a significant effect on Purchasing Decisions. The result of the f-test show that simltaneosly all independent variables, consisting of the Price variable (X1) and promotion variable (X2), had a significant effect on the Purchasing Decision variable. The result of the Determination analysis show that the two independent variables in this study were able to explain the fluctantion of Purchasing Decions by 45.5%.